Roasted-Coffee Aroma Sensing by Using Polymethyl Methacrylate (PMMA) and Polymethyl Methacrylate-Reduced Graphene Oxide (PMMA-rGO) Composite-based Quartz Crystal Microbalance (QCM) Sensor - Chrismiadi Nalle, Ferry; Sabarudin, Akhmad; Saputra, Aditya Ilham; Romdhoni, Alim; Khusnah, Nike Fitayatul; Sakti, Setyawan Purnomo (Trends in Sciences, 2025)
The primary quality of food is often associated with its physical attributes, particularly aroma. Key volatile compounds play a critical role in determining food quality. Coffee as a high-potential commodity in Indonesia and in the world strongly depends on their aroma as a signature for its quality. Several methods have been performed to determine the quality of coffee like cupping methods and chromatography-based technologies. But it depends on the coffee-experts who cannot be replicated by other people because of their subjectivity and still need complex sample processing and lengthy time-analysis. QCM sensor paves the way to solve this problem. By modification of its surface with nanomaterials, QCM sensing performance significantly can be elevated. This study aimed to detect the aroma of roasted coffee using a QCM-based electronic nose sensor. The QCM sensor was coated with aroma-sensitive materials to improve its sensing capabilities, specifically PMMA and PMMA-rGO composites. Both PMMA and PMMA-rGO were synthesized via an in situ polymerization method utilizing a binary solvent system in optimized proportions. The surface roughness of the QCM sensor was slightly higher when coated with PMMA-rGO (Sa = 493.68 ± 74.23 nm) compared to PMMA (Sa = 446.02 ± 26.19 nm) alone. The incorporation of rGO significantly enhanced the sensitivity of the QCM sensor towards the roasted coffee aroma. Based on the Sauerbrey calculation, the value of ∆f for PMMA is –66.05 ± 28.77 Hz while for PMMA-rGO is –74.28 ± 36.40 Hz. These findings suggest that PMMA-rGO composites hold considerable promise as effective sensing materials for improving QCM sensor performance. HIGHLIGHTS PMMA and PMMA-rGO composites were synthesized using modified in situ polymerization in the presence of a binary solvent. PMMA and PMMA-rGO were used as sensitive materials on the surface of the QCM sensor. The PMMA- and PMMA-rGO-coated QCM sensors detected roasted coffee aroma at 220 °C roasting temperature. GRAPHICAL ABSTRACT